Organic management in apple orchards: Higher impacts on biological control than on pollination. Issue 6 (24th August 2018) - Porcel, Mario; Andersson, Georg K. S.; Pålsson, Joakim; Tasin, Marco
Abstract: Intensive agricultural management negatively affects both natural enemies of pests and pollinators. Such management also has the potential to adversely affect the ecosystem services that these communities confer. Organic management has been proposed as an alternative method to mitigate such problems by restoring the services provided by arthropod communities. We evaluated the effect of organic management on two ecosystem services provided by arthropods in apple orchards: pollination and biological control. We used relative decrease in colonies to assess biological control of the major apple aphid pest, and measured pollination through fruit set, number of seeds per apple and pollinator visitation. Additionally, we monitored the organisms responsible for pollination and biological control services and established the impact of pollination on apple quality. Our results show a strong effect of organic management on biological control and on the temporal dynamic of natural enemy–pest interactions. Parameters such as aphid colony suppression, first and repeated occurrence of natural enemies, natural enemy species evenness and natural enemy abundance were significantly higher in organic compared to conventional orchards. Predatory bugs were the natural enemies best‐affected by organic management and played a key role in early predation of aphids preventing colony growth. In this instance, pollination was not influenced by organic management. It is likely due to the temporal scale at which this service is delivered, a scale that differs greatly from biological control, combined with differences in the dispersal capacity of the organisms involved. Fruit weight, calcium, potassium and magnesium content were positively affected by pollination success. Synthesis and applications . We found that organic management in apple orchards preserves the local natural enemy community, and specifically predatory bug populations, essential for early aphid colony suppression. Our results suggest that, in conventional orchards, local management options that decrease or even eliminate pesticide use early in the season would increase the biological control of aphids. This would lead to reduction in apple damage at harvest. Our results on pollination success indicate that the implementation of organic management at orchard scale does not enhance pollination services for apple growers. Abstract : We found that organic management in apple orchards preserves the local natural enemy community, and specifically predatory bug populations, essential for early aphid colony suppression. Our results suggest that, in conventional orchards, local management options that decrease or even eliminate pesticide use early in the season would increase the biological control of aphids. This would lead to reduction in apple damage at harvest. Our results on pollination success indicate that the implementation of organic management at orchard scale does not enhance pollination services for apple growers.